Self-esteem and depression in adolescents - M. Minev (Trakia Journal of Sciences)
PURPOSE. The article looks at self-esteem and depression during adolescence. It is a theoretical study of the relationship between depression and self-esteem. There are types of self-esteem, self-esteem by gender and age. The theories of depression in adolescence, as well as the factors leading to depression, are examined. Several scales for assessing depression are presented. In view of the application of the main features of self-esteem and depression, their intersections in practical context are examined.